2007
DOI: 10.1016/j.tiv.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Diepoxybutane activates the mitochondrial apoptotic pathway and mediates apoptosis in human lymphoblasts through oxidative stress

Abstract: Diepoxybutane (DEB) is the most potent metabolite of the environmental chemical 1, 3-butadiene (BD), which is prevalent in petrochemical industrial areas. BD is a known mutagen and human carcinogen, and possesses multi-systems organ toxicity. We recently reported that DEB-induced cell death in TK6 lymphoblasts was due to the occurrence of apoptosis, and not necrosis. In this study, we investigated the molecular mechanisms responsible for DEB-induced apoptosis in these cells. Bax and Bak were found to be over-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
3
25
1
Order By: Relevance
“…The determination of the mechanism of DEB-induced p53 accumulation contributes toward the understanding of the molecular toxicity of DEB and butadiene. Since DEB-induced p53-mediated apoptosis in human TK6 lymphoblasts has previously been described [19,39,73], these studies are a necessary prerequisite to the understanding of the role p53 plays in DEB-induced apoptosis in this experimental system as well as other DEB systems.…”
Section: Discussionmentioning
confidence: 91%
“…The determination of the mechanism of DEB-induced p53 accumulation contributes toward the understanding of the molecular toxicity of DEB and butadiene. Since DEB-induced p53-mediated apoptosis in human TK6 lymphoblasts has previously been described [19,39,73], these studies are a necessary prerequisite to the understanding of the role p53 plays in DEB-induced apoptosis in this experimental system as well as other DEB systems.…”
Section: Discussionmentioning
confidence: 91%
“…There are a great many evidences that ROS can induce apoptosis via several pathways, including either mitochondria-dependent or mitochondria-independent pathway in various cells and tissues (Krumschnabel et al, 2005;Wang et al, 2007;Yadavilli et al, 2007). In animal cells, previous results have demonstrated that MC-LR-induced rapid ROS generation led to apoptosis of primary rat hepatocytes through mitochondria-dependent pathway (Ding et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…20,22 A recent study has shown the abnormal cell cycle distribution of human lung cells with DEB treatment. 48 These data indicated the possible presence of a relationship between oxidative stress and adverse effects of germ cells in DEB exposure.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As shown in Figure 1C, it was revealed that compared with the control, the cell proportion in the G 2 /M phase was accumulated significantly accompanied by a decrease in the G 0 /G 1 phase after exposure to DEB with 100, 300, and 500 μM for 24 h. For DEB, previous studies have reported that DEB possesses an apoptosis-inducing ability in human lymphoblasts. 22,27 On the basis of this, we assumed that DEB might play an important role in the inhibition of cell growth in vitro. In order to determine whether the growth decrease in DEB-treated GC-2 cells was due to apoptotic death, we tested the effect of DEB on apoptosis using flow cytometry.…”
Section: Deb Inhibits Cell Proliferation and Induces G 2 Phasementioning
confidence: 99%
See 1 more Smart Citation